The University extension as an opportunity for joint action by undergraduate and graduate students during the COVID-19 pandemic - Villa Deléo, Rhayra Alani; do Amaral, Priscila Cristian; Santos Costa, Marina Luiza; Rachid Novaes, Rommel Larcher; Rezende de Oliveira, Aline; de Souza, Gladis Azevedo Cardoso; Corrêa Café, Ana Carolina; Sousa Nogueira, Leilismara; da Silva, Eduardo Sergio (Guará Journal, 2022)
This article aims to demonstrate the importance of outreach projects for university students, professionals, and the community involved. Through the selection of students, who receive comprehensive guidance, and through collaboration with a multidisciplinary team, the project aimed to enhance academic development and training, as well as provide comfort to patients. The positive impact on the education of participating students is evident, as well as the importance of post-COVID monitoring.
Keywords: COVID-19; University extension; Health post-graduate programs; Preceptorship